Giải phương trình: $(3x + 2)\sqrt{2x – 3} = 2x^{2} + 3x – 6$

Question

Giải phương trình: $(3x + 2)\sqrt{2x – 3} = 2x^{2} + 3x – 6$

in progress 0
Madeline 2 tháng 2021-07-23T04:15:55+00:00 1 Answers 4 views 0

Answers ( )

    0
    2021-07-23T04:17:21+00:00

    Đáp án:

     

    Giải thích các bước giải:

     ĐK: `x \ge 3/2`

    Đặt `\sqrt{2x-3}=t\ (t \ge 0)`

    `⇒t^2+3=2x`

    `t^2-(3x+2)t+2x^2+x-3=0`

    `Δ=[-(3x+2)]^2-4.1.(2x^2+x-3)`

    `Δ=9x^2+12x+4-4(2x^2+x-3)`

    `Δ=x^2+8x+16`

    `Δ=(x+4)^2 > 0 ∀ x`

    `⇒ t_{1}=2x+3,t_2=x-1`

    `t=2x+3⇒\sqrt{2x-3}=2x+3⇔2x-3=4x^2+12x+9⇔4x^2+10x+12=0` (vô nghiệm)

    `t=x-1⇒ \sqrt{2x-3}=x-1⇔ 2x-3=x^2-2x+1⇔x^2-4x+4=0⇔x=2\ (TM)`

    Vậy `S={2}`

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )